Decomposition of Supermassive Black Hole host galaxies in near-infrared - Babooram, Chantal (My University, 2025)
The co-evolution between black holes and galaxies is still poorly understood to this day. The black hole properties have been known to correlate with properties of their host galaxies. Over the years, there has been an increase in super massive black hole measurements, which leads to more detailed observational analysis and understanding of black holes and their evolution with their host galaxy. Using deep near infrared (NIR) imaging from the TNG telescope of a sample of black hole host galaxies, this thesis aims to produce galaxy decompositions into the bulge and disk components to further understand the Black hole mass and their host galaxy correlation. The NIR imaging provides the advantage of reducing effects of the dust obscuration. In this thesis we obtain sub-arcsecond resolution near-infrared data for 9 galaxies. Galaxy decomposition was performed on the data set, where the bulge parameter was obtained through the use of the program GALFIT. The data showed similar correlations to other papers, suggesting the black hole masses correlate with the host galaxy bulge luminosity.
Keywords: Galaxies, Black Holes, GALFIT, TNG telescope